Effectiveness of acupuncture and moxibustion compared with electroacupuncture and moxibustion in older people with gonarthrosis - MF, Enachescu (Revista Fisioterapia Invasiva / Journal of Invasive Techniques in Physical Therapy, 2019)
Background Gonarthrosis is a subtype of arthrosis which produces greater functional disability in our context. Women are more affected, with a prevalence in the general population of 16% and a clear increase as age advances, reaching up to 43%.Aims To evaluate whether the combined treatment of electroacupuncture and moxibustion is more effective than the treatment of acupuncture and moxibustion in patients of advanced age with gonarthrosis.Material and Methods An experimental, prospective and randomized study. Patients were divided into two groups: group A, who received acupuncture (n = 6) and group EA who received electroacupuncture (n = 7): modulated TENS (F = 5 Hz, P = 50 µS, I = 90%, 10 min). Both group A and EA combined treatments with moxibustion. Three interventions were performed, over three consecutive weeks, and the results obtained in each group were compared using several validated scales.Results 84.6% of patients were women, with a mean age of 83.3 years, and 53.8% of these with obesity. The right leg was the more affected (76.9%) and 46.2% had a severe disability. Pain reduction (Visual Analog Scale) was statistically significant in each session in both groups however, to a greater extent in group EA (reduction of pain EA 3.4 versus 1.3 in A). The improvements of stiffness with both treatments was evident (mean 69.2%), however without statistically significant between-group differences. A clear difference was not found in the functionality according to the different scales applied (WOMAC, Barthel, Katz, Up&Go) nor in the reduction in the use of medication.Conclusion The results obtained show a clear improvement in the control of pain and rigidity with the combination of both therapies, although differences were not found in the functionality and muscle strength scales, which are values that we believe would improve with a greater sample and a greater duration of interventions. In conclusion, in our study, electroacupuncture combined with moxibustion provides slightly better results to acupuncture combined with moxibustion, regarding the improvement of pain and stiffness in older patients with gonarthrosis.Introducción y objetivos La gonartrosis es el subtipo de artrosis que produce mayor discapacidad funcional en nuestro medio. Afecta más al sexo femenino, con prevalencia en población general de un 16% y un claro incremento a medida que avanza la edad pudiendo llegar hasta un 43%.Objetivos Evaluar si el tratamiento combinado de la electroacupuntura y moxibustión es más eficaz que el tratamiento de acupuntura y moxibustión en pacientes de edad avanzada con gonartrosis.Material y métodos Estudio experimental, prospectivo y aleatorizado. Los pacientes fueron divididos en dos grupos: grupo A al que se aplicó acupuntura (n = 6) y grupo EA al que se le aplicó electroacupuntura (n = 7): TENS modulado (F = 5 Hz, P = 50 µS, I = 90%, 10 min.), ambos combinados con moxibustión. Se realizaron tres intervenciones, en tres semanas consecutivas, y se compararon los resultados obtenidos en cada grupo a través de diversas escalas validadas.Resultados El 84,6% de los pacientes fueron mujeres, con edad media de 83,3 años, y un 53,8% de ellas con obesidad. La rodilla más afectada fue la derecha (76,9%) y el 46,2% registró una incapacidad severa. La reducción del dolor (Escala Visual Analógica) fue estadísticamente significativa en cada una de las sesiones en ambos grupos pero en mayor medida en el grupo EA (reducción del dolor EA 3,4 versus 1,3 en A). La mejoría en la rigidez con los dos tratamientos fue evidente (media de 69,2%) pero sin diferencias estadísticamente significativas entre ellas. No se determinó una diferencia clara en la funcionalidad en las diversas escalas aplicadas (WOMAC, Barthel, Katz, Up&Go) ni en la reducción en el consumo de fármacos.Conclusión Los resultados obtenidos muestran una clara mejoría en el control del dolor y de la rigidez con ambas combinaciones de terapias, aunque no se evidencien diferencias en las escalas de funcionalidad y fuerza muscular, valores que creemos mejorarían con una muestra más grande y mayor duración de las intervenciones.Así mismo podemos concluir que, en nuestro estudio, la electroacupuntura combinada con moxibustión ofrece resultados ligeramente superiores a la acupuntura combinada con moxibustión en cuanto a la mejoría del dolor y de la rigidez en pacientes ancianos con gonartrosis.
Keywords: acupuncture; electroacupuncture; moxibustion; gonarthrosis